Interventional Bronchus Occlusion Using Amplatzer Devices – A Promising Treatment Option for Children with Persistent Air Leak - Schütz, Katharina; Happel, Christoph M.; Keil, Oliver; Dingemann, Jens; Carlens, Julia; Wetzke, Martin; Müller, Carsten; Köditz, Harald; Griese, Matthias; Reiter, Karl; Schweiger-Kabesch, Andrea; Backendorf, Alexander; Scharff, AnnaZychlinsky; Bertram, Harald; Schwerk, Nicolaus (Klinische Pädiatrie, 2022)
Background: Persistent air leak (PAL) is a severe complication of secondary spontaneous pneumothorax (SSP). Surgical interventions are usually successful when medical treatment fails, but can be associated with significant complications and loss of potentially recoverable lung parenchyma. Methods: Retrospective analysis of efficacy and safety of interventional bronchus occlusions (IBO) using Amplatzer devices (ADs) in children with PAL secondary to SSP. Results: Six patients (four males, 4–15 years of age) underwent IBO using ADs as treatment for PAL. Necrotizing pneumonia (NP) was the most common cause (n=4) of PAL. Three patients were previously healthy and three suffered from chronic lung disease. All patients required at least two chest tubes prior to the intervention for a duration of 15–43 days and all required oxygen or higher level of ventilatory support. In three cases, previous surgical interventions had been performed without success. All children improved after endobronchial intervention and we observed no associated complications. All chest tubes were removed within 5–25 days post IBO. In patients with PAL related to NP (n=4), occluders were removed bronchoscopically without re-occurrence of pneumothorax after a mean of 70 days (IQR: 46.5–94). Conclusion: IBO using ADs is a safe and valuable treatment option in children with PAL independent of disease severity and underlying cause. A major advantage of this procedure is its less invasiveness compared to surgery and the parenchyma- preserving approach.
Keywords: air leak; persistent bronchopleural fistula; interventional bronchus occlusion; secondary spontaneous pneumothorax; pneumothorax; Amplatzer devices